Antimicrobial Activity and Essential Oil Composition of a New T. argyrophyllum (C. Koch) Tvzel var. argyrophyllum Chemotype - Polatoglu, Kaan; Demirci, Fatih; Demirci, Betuel; Goereni, Nezhun; Baser, Kemal Huesnue Can (JAPAN OIL CHEMISTS SOC, 2010)
Water-distilled essential oils from flowers and stems of Tanacetum argyrophyllum var. argyrophyllum from Turkey were analyzed by GC and GC/MS. The flower oil of T argyrophyllum var. argyrophyllum was characterized with camphor 29.7%, borneol 12.0%, 1,8-cineole 8.4% and bornyl acetate 6.1%. Stem oil was characterized with camphor 26.6%, 1,8-cineole 17.5%, and borneol 15.0%. Our previous research and literature on the essential oil of this plant reported oils with high thujone content unlike the present study. Antibacterial activity of the oils were evaluated for five Gram-positive and five Gram-negative bacteria by using a broth microdilution assay. The highest inhibitory activity was observed against Bacillus cercus for stem oil (125 mu g/mL) when compared with positive control chloramphenicol it showed the same inhibition potency. However, the same oil showed lower inhibitory activity against B. subtilis. The flower oil did not show significant activity against the tested microorganisms. DPPH radical scavenging activity of the T argyrophyllum var. argyrophyllum oil was investigated at 15 and 10 mg/mL concentrations. However, the oils did not show any significant activity when compared to positive control alpha-tocopherol. Both of the oils showed toxicity to Vibrio fischeri in the TLC-bioluminescence assay.
Keywords: Tanacetum argyrophyllum var. argyrophyllum; Asteraceae; essential oils; camphor; borneol; 1,8-cineole; bornyl acetate; chemotypes; DPPH radical scavenging; antibacterial activity; Vibrio fischeri toxicity; TANACETUM-VULGARE L.; SCHULTZ BIP.; BACILLUS-CEREUS; CHILIOPHYLLUM; GRIERSON; Chemistry; Food Science & Technology